The Effect of ESG, Cost of Capital, and Woman Board on Indonesia Firm Performance - Cendana, Puswita; Prayogo, Enny (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
In this study, the primary objective is to examine the influence of ESG (Environmental, Social, and Governance), cost of capital, and woman board on firm performance of Indonesian companies. The OLS (Ordinary Least Square) approach is used in this study to examine how ESG, cost of capital and woman board affect firm performance, which is assessed through the measurement of Return on Assets (ROA). The companies listed in the Thomson Reuters database with an observation period between 2020 until 2022 make up this study's population, and sample data was acquired through the application of purposive sampling method, totaling 117 samples. According to the research results, it is inferred that ROA is impacted significantly negative by ESG; cost of capital and woman board give such a significant and positive influence toward ROA. The unique feature of this research is its focus on a developing country, particulary Indonesia, in contrast to prior research that primarily focused on developed countries like Hong Kong.